2021
DOI: 10.1002/vrc2.13
|View full text |Cite
|
Sign up to set email alerts
|

Hymenoptera venom immunotherapy without human serum albumin as a stabilizer in a canine patient

Abstract: A four‐month‐old female Beagle, with a history of repeated anaphylactic reactions, was managed with venom immunotherapy (VIT), based on the results of a blood allergy test. Because there is a lack of VIT for dogs, a product from human medicine was used, which requires human serum albumin (HSA) in the solvent as a stabilizer. HSA has been described to cause sensitization and anaphylactic reactions, as well as other adverse effects in dogs. To avoid such adverse effects, water for injection was used as a solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Two previously reported case reports of Hymenoptera hypersensitivity utilised a canine-validated European laboratory that had facilities to perform CCD inhibition assays (ELISA; Fcε-Receptor technology; Laboklin GmbH & Co. KG). 11,23 Access to this laboratory was cost-prohibitive as a consequence of the author's geographical location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previously reported case reports of Hymenoptera hypersensitivity utilised a canine-validated European laboratory that had facilities to perform CCD inhibition assays (ELISA; Fcε-Receptor technology; Laboklin GmbH & Co. KG). 11,23 Access to this laboratory was cost-prohibitive as a consequence of the author's geographical location.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory used in this study could not perform CCD inhibition assays and thus we could not determine the role of CCDs in accounting for the false‐positive sIgE results. Two previously reported case reports of Hymenoptera hypersensitivity utilised a canine‐validated European laboratory that had facilities to perform CCD inhibition assays (ELISA; Fcε‐Receptor technology; Laboklin GmbH & Co. KG) 11,23 . Access to this laboratory was cost‐prohibitive as a consequence of the author's geographical location.…”
Section: Discussionmentioning
confidence: 99%
“…One publication reported that the majority of adverse reactions to VIT in dogs were mild and infrequent, occurring in 2.8% of 1944 venom injections administered during induction and maintenance VIT in 82 dogs 10 . Single case reports of dogs receiving VIT for 5 years and 2.9 years, respectively, report no adverse reactions 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…10 Single case reports of dogs receiving VIT for 5 years and 2.9 years, respectively, report no adverse reactions. 12,13 The objective of this study was to evaluate the safety of a modified rush VIT protocol in dogs as determined by the frequency and severity of adverse reactions. We hypothesised that rush VIT would be safe in dogs, with a low frequency of adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the recommended duration for VIT in humans is 5 years or even life-long in patients with high risk of future bee stings [14,15]. In dogs, it was shown that VIT was well-tolerated in conventional and rush protocols, but prospective controlled trials on the efficacy are missing [3,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%